Students’ and Teacher’s Difficulties in Dealing with Real-context Problem: a Case Study - Fardah, Dini Kinati; Kusumah, Yaya Sukjaya (Journal of Honai Math, 2025)
One of the goals of students studying mathematics is so that students have the ability to solve everyday problems. This ability leads to what is known as mathematical literacy. This article aims to describe the difficulties of teachers in activating mathematical literacy in the classroom and the difficulties of students in solving real-world context problems. This is a case study in a private school in Bandung, Indonesia. Eighteen students and their mathematics teachers were selected as subjects in this study. The results showed that students had difficulty understanding problems, especially non-routine problems that related to real-world contexts, even though they claimed to be familiar with the context given. In addition, students also had difficulty with the prerequisite material to solve the contextual problems given. Facing problems that they were unfamiliar with caused their confidence in solving problems to decrease when compared to their initial level of confidence. Meanwhile, for teachers, students' low reading interest, low reading comprehension, and low reasoning ability were problems for them. Designing a series of activities brought from real-world contexts in open-ended problem types that require reasoning and higher-order thinking skills can be a tool for students to develop mathematical literacy and can help teachers to implement it in their classrooms.